Crossing borders to facilitate live donor kidney transplantation: the Czech‐Austrian kidney paired donation program – a retrospective study. (23rd June 2020) - Viklicky, Ondrej; Krivanec, Sebastian; Vavrinova, Hana; Berlakovich, Gabriela; Marada, Tomas; Slatinska, Janka; Neradova, Tereza; Zamecnikova, Renata; Salat, Andreas; Hofmann, Michael; Fischer, Gottfried; Slavcev, Antonij; et al.
Summary: Kidney paired donation (KPD) is a valuable tool to overcome immunological barriers in living donor transplantation. While small national registries encounter difficulties in finding compatible matches, multi‐national KPD may be a useful strategy to facilitate transplantation. The Czech (Prague) and Austrian (Vienna) KPD programs, both initiated in 2011, were merged in 2015. A bi‐national algorithm allowed for ABO‐ and low‐level HLA antibody‐incompatible exchanges, including the option of altruistic donor‐initiated domino chains. Between 2011 and 2019, 222 recipients and their incompatible donors were registered. Of those, 95.7% (Prague) and 67.9% (Vienna) entered into KPD registries, and 81 patients received a transplant (95% 3‐year graft survival). Inclusion of ABO‐incompatible pairs in the Czech program contributed to higher KPD transplant rates (42.6% vs. 23.6% in Austria). After 2015 (11 bi‐national match runs), the median pool size increased to 18 pairs, yielding 33 transplants (8 via cross‐border exchanges). While matching rates doubled in Austria (from 9.1% to 18.8%), rates decreased in the Czech program, partly due to implementation of more stringent HLA antibody thresholds. Our results demonstrate the feasibility of merging small national KPD programs to increase pool sizes and may encourage the implementation of multi‐national registries to expand the full potential of KPD.